2006
DOI: 10.1086/498343
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Elucidation of the Unusually High [HNC]/[HCN] Abundance Ratio in Interstellar Space: Two‐dimensional and Two‐State Quantum Wave Packet Dynamics Study on the Branching Ratio of the Dissociative Recombination Reaction HCNH++e→ HNC/HCN + H

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…There are various theoretical studies of the DR reaction of HCNH + leading to similar results despite disagreement for the mechanism which involves either a direct formation pathway (Talbi & Ellinger 1998, Hickman et al 2005 or an indirect process (Shiba et al 1998, Taketsugu et al 2004, Ishii et al 2006 as these authors found no possibility for the direct process. However all studies of the direct and indirect processes lead to similar branching ratios for HCN and HNC formation.…”
Section: Resultsmentioning
confidence: 79%
“…There are various theoretical studies of the DR reaction of HCNH + leading to similar results despite disagreement for the mechanism which involves either a direct formation pathway (Talbi & Ellinger 1998, Hickman et al 2005 or an indirect process (Shiba et al 1998, Taketsugu et al 2004, Ishii et al 2006 as these authors found no possibility for the direct process. However all studies of the direct and indirect processes lead to similar branching ratios for HCN and HNC formation.…”
Section: Resultsmentioning
confidence: 79%
“…The theoretical results presented in Talbi & Herbst (1998) and Herbst et al (2000), and more recently by Hickman et al (2005) and Ishii et al (2006), show quite convincingly that the HNC/HCN abundance ratio resulting from the chemical reactions known to be effective in dark clouds cannot differ significantly from unity. There are two possible explanations for the discrepancy between the observations and theoretical predictions.…”
Section: The Chemical State Of Cha-mms1 and The Hnc/hcnmentioning
confidence: 76%
“…Recent theoretical studies corroborate Based on observations collected at the European Southern Observatory, La Silla, Chile, and at the Parkes Observatory operated by the Australia Telescope National Facility (ATNF). the equal branching ratios for HCN and HNC in dissociative recombination (Hickman et al 2005;Ishii et al 2006). HNC/HCN column density ratios clearly larger than unity have been reported: Churchwell et al 1984 find that [HNC]/[HCN] may be as high as ∼10 in some dark clouds cores, and Hirota et al (1998) find a ratio of ∼5 in L1498.…”
Section: Introductionmentioning
confidence: 99%
“…Although no such experiments have been performed on HNC, the results obtained for HCN provide relevant information also for the highly excited vibrational states of HNC. Hirano et al [9,12] and also Ishii et al [13] found theoretically that the neutral products HCN and HNC are formed in their ground electronic states after the dissociative recombination. The majority of the internal energy would be carried away as the vibrational energy.…”
Section: Discussionmentioning
confidence: 94%
“…A direct trajectory simulation for the dissociative recombination reaction at the Hartree-Fock level was made by Tachikawa [11]. Extensive ab initio dynamics calculations were carried out to elucidate the details of the reaction processes and the branching ratio of 1 was obtained [12,13]. On the other hand, Talbi and Ellinger [14] and more recently Hickman et al [15] proposed a direct dissociative recombination mechanism.…”
Section: Introductionmentioning
confidence: 99%